Do Non-Standard Working Hours Cause Negative Health Effects? Some Evidence from Panel Data - Ulker, A (My University, 2006)
What does the around-the-clock economic activity mean for workers’ health? Despite the fact that non-standard work accounts for an increasing share of the job opportunities, relatively little is known about the potential consequences for health and the existing evidence is ambiguous. In this paper I examine the relationship between non-standard job schedules and workers’ physical and mental health outcomes using longitudinal data from the Household, Income and Labour Dynamics in Australia (HILDA). Specifically, the four health indicators considered are self-rated health and the SF-36 health indices for general health, mental health and physical functioning. In terms of direction of the effects, overall results generally suggest a negative relationship between non-standard work schedules and better health for both males and females. Regarding the statistical significance and magnitudes of the effects, however, we observe apparent differences between males and females. Among females, most of the coefficients in all models are statistically insignificant, which implies very small magnitudes in terms of the correlation between non-standard working hours and health. These results apply uniformly to all health measures investigated. Among males, on the other hand, the negative relationship is more noticeable for self-rated health, general health and physical functioning than for mental health. The pooled OLS and random effects coefficients are usually larger in magnitude and more significant than the fixed effects parameters. Nonetheless, even the more significant coefficients, fortunately, do not imply large effects in absolute terms.
Centre for Economic Policy Research, Australian National University, Discussion Paper
Keywords: Health; Employment; Employment -- Hours; Health and wellbeing; Labour market; Health; Employment and unemployment